Highly Flexible Infrared Emitter with Spatially Controlled Emissivity for Optical Security (Adv. Mater. Technol. 4/2023). Issue 4 (24th February 2023) - Kang, Dongkyun; Kim, Yeongseon; Kim, Chanhee; Lee, Myeongkyu
Abstract : Infrared Emitters In article number 2200808, Myeongkyu Lee and co‐workers present a Ge2 Sb2 Te5 (GST)‐ based infrared emitter that is fabricated on a flexible substrate such as plastic and paper, and its emissivity is space‐selectively controlled using a spatially modulated pulsed laser beam. The multispectral properties of GST enable different visible and thermal images to be simultaneously printed in the same area of the emitter. This provides a promising feature for optical security, including anti‐forgery.